Erythema nodosum as a manifestation of many systemic diseases - Kojder, Dominika; Pawlak, Weronika; Szymańska, Julia; Musiał, Lena; Możdżyńska, Agnieszka; Kapłon, Kamil; Kamińska, Izabela; Rymarz, Anna; Frączek, Paulina; Sołtys, Mirosław (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Erythema nodosum is a most frequent form of panniculitis and it appears as erythematous, painful rounded, nodules typically localized on the pretibial area. The purpose of our review is to present diseases that can be underlying causes of erythema nodosum and to draw attention to accompanying symptoms that can guide us to the appropriate diagnosis. Brief description of the state of knowledge: Currently, erythema nodosum is thought to be a symptom associated with hypersensitivity reactions to various antigens. Although the majority of the causes are considered idiopathic, erythema nodosum may be caused by many etiological factors. Summary: Erythema nodosum is usually an acute condition that resolves without treatment. However, it can sometimes be the first sign of a serious condition - autoimmune diseases, infections or malignancy. In such cases it is essential to observe it carefully and implement appropriate diagnostics that allow us to make a correct diagnosis.